Assessing the Effects of Natural Resources on Long-Term Growth : An Extension of the World Bank Long Term Growth Model - Loayza, Norman V.; Galego Mendes, Arthur; Mendez Ramos, Fabian; Pennings, Steven Michael (Washington, DC: World Bank, 2022)
This paper extends the World Bank's Long-Term Growth Model (LTGM) with the addition of a natural resource sector to analyze how long-run growth evolves in resource-rich countries and the growth impacts of price shocks and resource discoveries. In the LTGM-Natural Resource Extension (LTGM-NR), commodity price shocks affect long-term economic growth through physical investment rates. As a large share of resource income typically accrues to the government, the size of the boost to investment in a price boom depends on the government’s fiscal rule. Fiscal rules that prioritize public investment, like a Hartwick Rule, generally lead to the largest increases in long-term growth. However, structural surplus rules, which save commodity revenues, can also boost growth if they free up savings for private investment. The response of growth to discoveries of natural resources is similar to the response to price shocks, although discoveries also produce a direct effect on real GDP, in addition to an indirect effect through investment. The LTGM¬-NR also captures the effect of other (non-resource) growth fundamentals in resource-rich economies, and it is better suited to general growth analysis in these countries than the standard LTGM. However, the LTGM-NR is a supply-side model, and so does not capture the short-run effects of price and discovery shocks that operate through aggregate demand.